The lean management systems handbook - Charron, Rich; Harrington, H.James; Voehl, Frank; Wiggin, Hal (CRC Press, 2014)
"This book presents a first of its kind approach that describes critical components for sustainable Lean management. The handbook shows how managers at all levels of the organization can integrate Lean into their daily management activities. It also defines the Lean philosophy, beliefs and behaviors required to develop a thriving Lean company culture. Packed with detailed examples and step-by-step instructions, it's the ideal handy reference guide to help mangers and leaders make the transition from the classroom to the field. It will feature brief summaries and examples of the most important tools in Lean management systems development"--Provided by Publisher